Composites as candidate materials for photovoltaic cells. (30th November 2022) - Olorunfemi, Tope R.; Nwulu, Nnamdi I.; Ismail, Sikiru O.
ABSTRACT: Composites are two or more materials with different properties joined together to manufacture a new material. The resulting physical and chemical properties of each constituent new material remain distinct with enhanced properties when compared to the individual constituent materials. Photovoltaic (PV) cells have been very important source of energy in recent years falling under renewable energy resources (RESs), meaning that they are abundant in nature and also environmentally friendly in producing electricity. PV cells contain tiny different types of silicon layers which when the sun shines through them cause reactions between the electrons. In this way, the movement of the electrons through them and around the circuit generates electricity. A lot of research has been done and still going on in the enhancement of the PV cells to optimise their application. Therefore, the objective of this study is to review and compare the current state-of-the-art articles on different types of composites, which have been used for the PV cell enhancement, especially some two-dimensional (2D) materials. Therefore, graphene and MoS used as nanocomposites are considered in this review to support appropriate and informed decisions that are made available to researchers and industries to know the best materials to use going forward in the manufacture of PV cells for better enhancement. A summary of these and more has been presented and prospected in this article.